(untitled) (Bangladesh Journal of Agricultural Research, 2009)
Field experiments were conducted at the research farm of Bangladesh Agricultural Research Institute, Joydebpur during kharif-1 (March to July) seasons of 2005 and 2006 to identify the critical period of crop-weed competition for Indian spinach. Major weed species were Paspalurn commersoni, Echinochlaa crusgalli. Lie nv/nc india. Cyanotis axillaris and Cyperus rotundus. The lowest weed dry matter was 76.3 g m-2 in 2005 and l01.60 g m-2 in 2006 from the plots weeded up to 40 days after transplanting (DAT). The highest yields were obtained (74.82 t ha in 2005 and 48.48 t ha in 2006) from the weed free plots. The fresh yield of Indian spinach did not vary among no weeding upto 20, 30 and 40 DAT in 2006. But weeded plot upto 30 and 40 DAT produced identical yield in 2005. Maximum BCR (4.52) was obtained from weeded plots upto 30 DAT in 2005 but BCR (2.60) was same from weeded upto 30 and 40 DA F in 2006. On an average, highest BCR (3.55) was recorded from weeding upto 30 DAT. Results revealed that the critical period of crop weed competition lies between 20 and 30 DAT and two times hand weeding would be necessary within 30 DAT for maximum benefit. Key Words: Crop-weed competitions, critical period, weed management and Indian spinach. doi: 10.3329/bjar.v33i4.2306 Bangladesh J. Agril. Res. 33(4) : 623-629, December 2008